Pretty baby [videorecording (DVD)] - Malle, Louis, 1932-1995; Malle, Louis, 1932-1995; Carradine, Keith, 1949-; Sarandon, Susan, 1946-; Shields, Brooke, 1965-; Faye, Frances; Fargas, Antonio, 1946- (Paramount, 2003)
A photographer obsessed with the prostitutes in New Orleans' red-light district in 1917 is bewitched by a twelve-year-old child prostitute.